Effect of liquid nitrogen freeze–thaw cycle on fracture toughness and energy release rate of saturated sandstone. (December 2021) - Hou, Peng; Su, Shanjie; Liang, Xin; Gao, Feng; Cai, Chengzheng; Yang, Yugui; Zhang, Zhizhen
Highlights: Multiple mode (I/II/mixed) fracture toughness experiments are performed on the saturated sandstone subjected to different LN2 freeze–thaw cycles. The energy release rate of the sandstone subjected to the LN2 freeze–thaw cycle is corrected by the P-wave velocity. The mode I fracture is more sensitive to the LN2 freeze–thaw cycle. Mode I fracture requires minimum applied energy and shows the maximum energy release rate, while mode II fracture is the opposite. Abstract: To enhance the ability of tight sandstone gas extraction, liquid nitrogen (LN2 ) freeze–thaw cycle method can be employed to improve the physical and mechanical properties of the sandstone. Rock fracture behaviors and mechanical properties after fracturing play an important role to successfully implement reservoir stimulation. Since tight sandstone gas reservoirs are usually characterized by high water content, the influences of LN2 freeze–thaw cycle on the fracture toughness and energy-release rate of the saturated sandstone are studied in this paper. The three-point bending experiment is carried out on the notched semicircular bending sandstone samples subjected to different LN2 freeze–thaw cycle times under three different modes, that is, mode I, mixed mode (I/II), and mode II. The structure damage and facture morphology analyses are performed to explain the differences in fracturing behaviors. The energy release rate of the saturated sandstone subjected to the LN2 freeze–thaw cycle is corrected by the P-wave velocity. The experimental results indicate that the LN2 freeze–thaw cycle can promote the weakening of cementation between mineral particles and produce microcracks inside the saturated sandstone, further resulting in an increase in the roughness of the crack surface after loading failure. For all three modes, the fracture toughness and the energy-release rate gradually decrease with the increase in the LN2 freeze–thaw cycle times. For all the LN2 freeze–thaw cycles, mode I requires the minimum applied energy for the fracture propagation, while mode II requires maximum applied energy. In the three modes, the energy-release rate in mode I is the largest. Compared with mixed mode and mode II, the fracture toughness and fracture energy of mode I are more sensitive to the LN2 freeze–thaw cycle. The fracture energy depends on both the microstructure characteristics inside rocks and the mechanism of the fracture propagation. The results are helpful to better understand the initiation and propagation of cracks during the sandstone gas extraction.